Advanced fluid indicator based on numerical simulation and deep learning - Liu, C. (Elsevier B.V., 2020)
Hydrocarbon reservoirs are commonly identified based on their elastic properties, with high success rates in many cases. However, the porosity and rock matrix may interfere with the fluid effect. The brine-saturated rock may have a similar response with the hydrocarbon reservoir, which cause misinterpretation. A new method, the âadvanced fluid indicatorâ method, is proposed to reduce the uncertainty in reservoir detection and characterisation by the rotation of the P-wave and shear moduli. This advanced fluid indicator exhibits the ability to identify the fluid type. The local empirical relationships are extracted from the well log data. Then the Monte Carlo forward modelling is constructed using the relationships. The advanced fluid indicator is calculated using the relative parameters. The correlation coefficient between the advanced fluid indicator and bulk modulus of the pore fluid reaches 0.9935 in the forward modelling, which indicates that the new method can be used to detect the fluid type directly. Deep learning is then applied to train a regression model using the rock physics dataset derived in the forward modelling. The advanced fluid indicator is calculated by the trained regression model using well log data. This method has been applied in S field in Malay Basin, South China Sea. It successfully detects all the reservoirs that are identified in the well log section. Furthermore, the advanced fluid indicator values indicate the fluid type of each reservoir. While the three currently used crossplot methods can also detect the three gas reservoirs, they are unable to separate the two oil reservoirs from non-hydrocarbon-bearing rocks clearly. Therefore, the proposed advanced fluid indicator method outlines an effective approach that combines hydrocarbon prediction and deep learning to detect and characterise hydrocarbon reservoirs with higher accuracy and lower ambiguity than current methods. Â© 2020 Elsevier B.V.